1978
DOI: 10.1172/jci109171
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Hyperactivity during Hypothalamic Stimulation in Spontaneously Hypertensive Rats

Abstract: A B S T R A C T To (2) found the vasodepressor effects produced by cutting neural connections between the hypothalamus and mesencephalon more pronounced in spontaneously hypertensive than in normotensive rats. Second, Buniag et al. (3) later showed that pressor responses elicited by electrical stimulation of the posterior hypothalamus were larger in awake rats with spontaneous hypertension than in normotensives or in those with deoxycorticosterone acetate-salt (Doca)l hypertension. How these differences are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Studies in our laboratory have demonstrated that bilateral dorsal rhizotomy (T-10 to L-2) prevents the development of hypertension and the increase in NE turnover rate and release in the posterior hypothalamic nuclei in CRF rats (41). This suggests that afferent impulses from damaged kidneys may activate areas of the brain involved in the noradrenergic regulation of blood pressure and contribute to the development of hypertension (42)(43)(44)(45)(46)(47). This notion is supported by the study of Converse et al (48) who showed that the decrease in arterial pressure after bilateral nephrectomy in uremic patients on chronic dialysis, was associated with lower sympathetic nerve firing and regional vascular resistance.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies in our laboratory have demonstrated that bilateral dorsal rhizotomy (T-10 to L-2) prevents the development of hypertension and the increase in NE turnover rate and release in the posterior hypothalamic nuclei in CRF rats (41). This suggests that afferent impulses from damaged kidneys may activate areas of the brain involved in the noradrenergic regulation of blood pressure and contribute to the development of hypertension (42)(43)(44)(45)(46)(47). This notion is supported by the study of Converse et al (48) who showed that the decrease in arterial pressure after bilateral nephrectomy in uremic patients on chronic dialysis, was associated with lower sympathetic nerve firing and regional vascular resistance.…”
Section: Discussionmentioning
confidence: 94%
“…There is also substantial evidence that an increase in noradrenergic activity in the posterior hypothalamus is associated with increased peripheral SNS activity and blood pressure. Electrical stimulation of the posterior hypothalamic areas increases blood pressure in the rat (42, 43,54), and destruction of these areas decrease blood pressure in SHR rats (55). Local perfusion of hypertonic saline or phenylephrine in the posterior hypothalamus elicited increased blood pressure, heart rate, and NE release (56).…”
Section: Discussionmentioning
confidence: 99%
“…7,15 A central disturbance in NE release by the hypothalamus is related to increased SNS activity. 8 Accordingly, augmented NE release and catecholamine synthesis as well as tyrosine hydroxylase gene expression have been reported at central sites related to blood pressure regulation in adult SHR.…”
Section: Discussionmentioning
confidence: 99%
“…The number of individual pulses per second was counted with a rate analyzer whose output was recorded as a histogram on an ink-writing recorder converted to digital form using a computer interface, and printed by a programmed calculator. 21 …”
Section: Sympathetic and Pressor Responsiveness In Anesthetized Ratsmentioning
confidence: 99%